From the ground up: Energetic and performance consequences of running shoe design choices - Frederick, E. C. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Various characteristics under the control of shoe designers and engineers can affect the energetic demands of running and enhance or diminish performance. Direct performance effects are documented and significant but indirect effects expressed via the energetic economy of running are also beneficial and thoroughly studied. Energetic consequences highlight a confluence of mechanics and energetics that flows from the ground, though the foot and shoe and as far up the chain as the runner.s head. The resonant properties and relative resilience of the shoe sole as well as the running surface can affect performance. Some of these effects are a consequence of tuning of the body with the surface/shoe. Other effects have been attributed to shoe mass and the distribution of mass, as well as the ability of the shoe to reduce the energetic cost of cushioning. Traction, as a means of maximizing the efficacy of running effort, and the bending stiffness of the sole also have been shown to influence performance - albeit via different biomechanical mechanisms. Even improved aerodynamics can offer some performance advantages. The design engineering of the running shoe, in particular the choice of shock attenuating materials and the architecture of the sole of the shoe, has the capacity to influence kinematic and kinetic responses which in turn influence energetic economy and perhaps enhance performance. It is possible, at this point, to prescribe certain shoe characteristics that should have a potential, positive performance benefit for the majority of runners, but even greater is the potential offered by customization and individualization. Individual responses to many of these manipulations in design can be highly variable, but these variable responses are measureable in some cases. There is evidence that mechanical properties can be tuned to individual biomechanics to maximize the potential benefit. Furthermore, potential performance improvements may be possible not only by customizing the shoe to address intrinsic, individual requirements, but also by adjusting the design of the shoe to be used for a given race, in anticipation of extrinsic, but performance-influencing, factors such as: ambient and surface temperature, wind direction and speed, course topography, expected traction requirements, and competition surface compliance. Although a benefit provided by any one performance-enhancing factor may be small, and arguably inconsequential, by itself, the greatest potential for using what we know to allow runners to run faster will come by embracing a multi-factorial approach. A convergence of multiple factors magnified by individualization and customization, can focus latent benefits on amplifying energetic economy and unleashing the human potential for running ever faster.